2015
DOI: 10.5505/tjtes.2015.53059
|View full text |Cite
|
Sign up to set email alerts
|

Saving the zone of stasis in burns with melatonin: An experimental study in rats

Abstract: BACKGROUND: Studies aimed at recovering the zone of stasis are one of the major issues of experimental burn studies. Many drugs including antithrombotics, anticoagulants, anti-inflammatories have been investigated experimentally for saving the zone of stasis. In this study, the effect of the systemic melatonin on the zone of stasis was evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In this study, we used the experimental model of zone of stasis, which was first described by Regas and Ehrlich (1,11). By calculating (a) the amount of living tissue macroscopically, (b) cell proliferation immunohistochemically by PCNA, and through (c) scintigraphic examination, we showed that the quercetin treatment, especially pre-burn, statistically significantly increased the viability of tissue in the zone of statis of a burn when compared to the control group.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In this study, we used the experimental model of zone of stasis, which was first described by Regas and Ehrlich (1,11). By calculating (a) the amount of living tissue macroscopically, (b) cell proliferation immunohistochemically by PCNA, and through (c) scintigraphic examination, we showed that the quercetin treatment, especially pre-burn, statistically significantly increased the viability of tissue in the zone of statis of a burn when compared to the control group.…”
Section: Discussionmentioning
confidence: 95%
“…After the appropriate antiseptic application, burns were created on the dorsum of each animal using a custommade steel comb with four rectangular rows (20x10 mm) and three interspaces (20x5 mm) weighing 150 gr pre-heated in boiling water for 15 minutes and applied without pressure for 20 seconds. This resulted in four rectangular 10×20 mm full-thickness burns separated by three 5×10 mm unburned interspaces representing the zone of stasis, according to the comb burn model defined by Regas and Ehrlich (11).…”
Section: Burn Proceduresmentioning
confidence: 99%
“…There is preliminary evidence that melatonin has benefits that limit burn wound damage. Data shows that, when given parentally, melatonin reduces cellular damage in the zone of stasis that surrounds the area of irreversible coagulation necrosis that is a result of a burn [152,153]. In particular, the histopathological examination of the zone of stasis revealed less edema and congestion, a reduced inflammatory response, and less fibrotic tissue generation, thereby limiting scar tissue.…”
Section: Melatonin In Burn Wound Damagementioning
confidence: 96%
“…MT can preserve the level of glutathione (GSH) within cells and in mitochondria, suppressing oxidative damage [42,43]. MT not only attenuates oxidative damage in experimental burns [44][45][46][47][48] but also in burn patients [49]. While previous research indicates that MT could be beneficial in instances of DOI after severe skin burn, a comprehensive review on this topic has yet to be performed.…”
Section: Introductionmentioning
confidence: 99%